PENGARUH EFEKTIVITAS SIA DAN KEMAMPUAN PENGGUNA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI PEMODERASI - Chrisnawan, I Rai Kevin Agustia; Suardana, Ketut Alit (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023DO - 10.24843/EEB.2023.v12.i09.p07, 2023)
In this digital era, the development of technology-based information systems is progressing very rapidly. The emergence of corporate awareness of the importance of using this technology has a good impact on the company. With the development of information systems, of course, every company is competing to use information systems to improve company performance. The purpose of this study is to analyze and provide empirical evidence regarding the effect of the effectiveness of accounting information systems and the ability of users to be moderated by work motivation on employee performance. The population in this study amounted to 36 people, the method of determining the sample using purposive sampling obtained a sample of 32 samples. In this study using multiple linear regression analysis techniques and Moderated Regression Analysis (MRA). The results of this study indicate that the effect of the effectiveness of the accounting information system has a positive and significant effect on employee performance and the user's ability has a positive and significant effect on employee performance. This study also found that work motivation strengthens the effect of the effectiveness of accounting information systems and user capabilities on employee performance.